SOME MOMENTS OF DISTORTION OF REALITY IN IRIS MURDOCH’S NOVEL “UNDER THE NET” - Ejupi, Vlera; Iseni, Arburim; Siljanovska, Liljana (European Scientific Journal, ESJ, 2014)
Life is full of adventures that we might be a victim of. Life is also a playful net which throws on ourselves interesting moments in order to make us face ourselves in the process of coping with them. This is the net which is thrown on us day after day, moment after moment, there are moments that we lose a complete view and reflect a lot of negative energy. On the other hand we try to create our own net, as a counter reflection of the first net, and thus put the two of them in a constant struggle. This is done to create our own reality. A reality which reflects our deep inner self which is in a constant struggle with the outer, already established reality. So it is up to us to make these kinds of struggles if we want to break free from the stultifying movements of the life waves.